ANALISIS DAMPAK DARI LITERASI DIGITAL DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN - Agnes Dwita Susilawati; Mei Rani Amalia (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
The purpose of this study is to determine whether the work environment and digital literacy of Honda Tegal Raya marketing personnel have an effect on their job happiness. This kind of research uses SPSS 24 and is quantitative in nature. Techniques such as observation, interviews, and questionnaires were used to gather data. Thirty-one permanent employees in the marketing department made up the population. Multiple Linear Regression Analysis was utilized to analyze the data. With a t-count value of 2.640 and a significance level of 0.014, the partial study's results indicate a positive and significant relationship between digital literacy and job satisfaction. Similarly, a t-value of 2.285 and a significance level of 0.030 demonstrate a positive and significant relationship between the work environment and job satisfaction. Employee job satisfaction was found to be positively and significantly impacted by digital literacy, as well as by the work environment. Additionally, employee job satisfaction was found to be positively and significantly impacted by both digital literacy and the work environment at the same time. The study's findings support the notion that digital literacy positively and significantly affects job satisfaction among Honda Raya Tegal employees working in the marketing department. Specifically, it demonstrates that higher an employee's proficiency with technology (digital literacy), the more content they will be with the work they produce. In the marketing department of Honda Raya Tegal, employees' job happiness is positively and significantly impacted by their work environment. This indicates that higher job satisfaction is correlated with a better work environment for employees. Both the work environment and digital literacy have a simultaneous impact on Honda Raya Tegal employees' job happiness in the marketing department.